(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article deals with the peculiarities of the love discourse manifestation in lyrical poetry of Mykola Voronyi. This poet is considered to be the unique representative of Ukrainian literature dated by the period of early modernism at the end of the 19th and the beginning of the 20th century. The paper defines and describes the aesthetic and thematic aspects of the love discourse, in particular, love for the motherland, the feeling of love to a person. Love for the motherland manifests itself first of all in understanding the image of the homeland as an attributively tragic concept. The feeling of love to a person is also marked by the tragedy and is mainly interpreted as the set of emotions coming after the loss of reciprocity. At the same time the paper notes the feature ambivalence of the selected thematic groups, especially it is marked by the interpretation not only in the tragic and elevated tonality, but also in the ironic and satirical ways. This article distinguishes, analyzes and interprets the artistic images, their content and functional load dominating in the poet’s lyrics devoted to the problems of love. The changes of literary discourse within the limits of folklore and individual and author imagery are considered and illustrated. Such observations allow determining the interaction between the oppositional features of early modernism (in particular, symbolism) and traditionalism in the poetic works of Mykola Voronyi.